Preparation of Renewable Epoxy-Amine Resins With Tunable Thermo-Mechanical Properties, Wettability and Degradation Abilities From Lignocellulose- and Plant Oils-Derived Components - Hollande, Louis; Do Marcolino, Izia; Balaguer, Patrick; Domenek, Sandra; Gross, Richard A.; Allais, Florent (Frontiers in Chemistry, 2019)
100% renewable triphenol - GTF - (glycerol trihydroferulate) and novel bisphenols - GDFx - (glycerol dihydroferulate) were prepared from lignocellulose-derived ferulic acid and vegetal oil components (fatty acids and glycerol) using highly selective lipase-catalyzed transesterifications. Estrogenic activity tests revealed no endocrine disruption for GDFx bisphenols. Triethyl-benzyl-ammonium chloride (TEBAC) mediated glycidylation of all epoxies afforded innocuous bio-based epoxy precursors GDFxEPO and GTF-EPO. GDFxEPO were then cured with conventional and renewable diamines, and some of them in presence of GTF-EPO. Thermo-mechanical analyses (TGA, DSC and DMA) and degradation studies in acidic aqueous solutions of the resulting epoxy-amine resins showed excellent thermal stabilities (Td5% = 282–310 °C), glass-transition temperatures (Tg) ranging from 3 to 62 °C, tunable tan α, and tunable degradability, respectively. It has been shown that the thermo-mechanical properties, wettability and degradability of these epoxy-amine resins can be finely tailored by judiciously selecting the diamine nature, the GTF-EPO content, and the fatty acid chain length.